Willingness-to-pay for community-based health insurance among informal workers in urban Bangladesh - Ahmed, Sayem; Enamul Hoque, Mohammad; Razzaque Sarker, Abdur; Sultana, Marufa; Islam, Ziaul; Gazi, Rukhsana; A. M. Khan, Jahangir (© 2016 Public Library of Science, 2016)
This article was published in PLoS ONE [© 2016 Public Library of Science] and the definite version is available at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0148211